Pengaruh Motivasi Belajar Siswa Terhadap Prestasi Belajar Matematika Kelas V SD Negeri 2 Tanduk Ampel Tahun Pelajaran 2015/2016 - Utomo, Arif Wahyu, Sri Hartini, S.H., M.Pd (2015)
This study aims to determine: the effect of students' motivation to learn mathematics achievement of fifth grade SD Negeri 2 Tanduk Ampel lesson year 2015/2016. This type of research is quantitative research experiment. Subjects in this study were all fifth grade students of SD Negeri 2 Tanduk Ampel lesson year 2015/2016. Data collection technique used is the technique of the questionnaire (questionnaire) and documentation. Test engineering instruments used are validity and reliability testing. The analysis technique used is preceded by t test analysis is the prerequisite test normality test. Based on the results of data analysis with significance level of 5% tobtained > ttable, namely 2.356> 2.002 with the average value of learning motivation of fifth grade SD Negeri 2 Tanduk Ampel l at 66.63. The conclusion of this study are as follows: no influence students' motivation to learn mathematics achievement of fifth grade SD Negeri 2 Tanduk Ampel lesson year 2015/2016.